2014
DOI: 10.1111/jgs.12987
|View full text |Cite
|
Sign up to set email alerts
|

Does the Introduction of Nursing Home Culture Change Practices Improve Quality?

Abstract: Objectives To understand whether nursing home (NH) introduction of culture change practices is associated with improved quality Design NH-level panel study using multivariate fixed-effects statistical modeling to estimate the effect of culture change introduction on quality outcomes Setting and Participants 824 U.S. NHs with culture change practice involvement beginning between 2005 and 2010 Measurements A culture change practice score (derived from a 2009/10 national NH survey) was used to stratify anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 26 publications
3
53
0
1
Order By: Relevance
“…21, 29, 30, 37, 38 Five studies showed CAUTI reduction 15, 22, 32, 34, 35 (1 significantly 34 ); nine studies showed UTI reduction 13, 18, 19, 21, 23–25, 27, 28, 31 (none significantly); 2 studies showed bacteriuria reduction (none significantly). One study 36 reported 2 composite outcomes including bacteriuria or CAUTI or death, with statistically significant improvement reported for 1 composite measure.…”
Section: Resultsmentioning
confidence: 98%
“…21, 29, 30, 37, 38 Five studies showed CAUTI reduction 15, 22, 32, 34, 35 (1 significantly 34 ); nine studies showed UTI reduction 13, 18, 19, 21, 23–25, 27, 28, 31 (none significantly); 2 studies showed bacteriuria reduction (none significantly). One study 36 reported 2 composite outcomes including bacteriuria or CAUTI or death, with statistically significant improvement reported for 1 composite measure.…”
Section: Resultsmentioning
confidence: 98%
“…17 Several studies have demonstrated the importance of changing the culture of an organization when implementing a new initiative. 18,19,20 This may include changing the philosophy of care thereby transforming an impersonal institution into a safe, caring community 21 or improving the quality of resident care. 19 In this paper we examine the barriers and facilitators to implementing the INTERACT™ program, many of which involved culture change, reported by representatives of 71 NHs randomized to the intervention group of a clinical trial of the INTERACT™ program.…”
Section: Change Modelmentioning
confidence: 99%
“…One recently reported study made a critical step toward filling this gap by exploring the association between the extent of culture change implementation and rates of resident hospitalization (Miller et al. ). The study found that the extent of culture change was negatively correlated with hospitalization rates.…”
mentioning
confidence: 99%
“…However, the authors noted that “further longitudinal studies examining the association between the extent and types of culture change practices implemented and changes in quality indicators are recommended” (Miller et al. , p. 1682).…”
mentioning
confidence: 99%